Dramatic Metabolic Response to Dual ICI With Chemotherapy in Low PD‐L1 NSCLC Case - Toshikazu Kumasa; Akina Nigi; Keisuke Iwamoto; Hidetoshi Itani; Shigeto Kondou (Respirology Case Reports)
ABSTRACT Despite low PD‐L1 (Programmed Death‐ligand 1) expression, this patient exhibited a dramatic positron emission tomography‐computed tomography response to dual immune checkpoint inhibitors with chemotherapy. This case highlights the potential benefits of combination therapy beyond traditional PD‐L1‐based treatment selection.